Deterministic field-free switching of perpendicular magnetization by spin–orbit torques originating from in-plane magnetized Co2MnAl - Daimu Morita; Takuya Hara; Michihiko Yamanouchi; Tetsuya Uemura (AIP Advances, 2023)
Spin–orbit torques (SOTs) induced magnetization switching in a perpendicularly magnetized CoFeB film deposited on a Ti/in-plane magnetized Co2MnAl stack was investigated. Deterministic switching of the CoFeB magnetization was demonstrated by applying a current pulse to the stack in a direction parallel or antiparallel to the Co2MnAl magnetization. We found that the hysteresis loops of the anomalous Hall resistance for CoFeB under the constant current is shifted in the out-of-plane magnetic field axis direction depending on the directions of both the applied current and the magnetization of Co2MnAl. The shift amount exhibits an almost linear increase as the current magnitude increases. These results are consistent with the effects caused by SOTs originating from spin currents having an in-plane polarization orthogonal to the Co2MnAl magnetization.